2007
DOI: 10.1111/j.1478-3231.2007.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of treatment withdrawal in type 1 autoimmune hepatitis

Abstract: Multiple relapses are associated with a poorer prognosis than sustained remission or single relapse episodes. Initial treatment to resolution of laboratory abnormalities may afford the greatest opportunity to prevent relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 51 publications
0
126
0
5
Order By: Relevance
“…An important finding in our study was that decreasing AST/ALT levels to less than 30 IU/L for men and less than 19 IU/L for women (instead of reducing AST/ALT levels to less than twice the normal value reported by the laboratory) lessened the risk of relapse. Other investigators have also reported this phenomenon (18,26). Long-term continuation of maintenance therapy for those in remission can also prevent relapse (18,26).…”
Section: Discussionmentioning
confidence: 90%
“…An important finding in our study was that decreasing AST/ALT levels to less than 30 IU/L for men and less than 19 IU/L for women (instead of reducing AST/ALT levels to less than twice the normal value reported by the laboratory) lessened the risk of relapse. Other investigators have also reported this phenomenon (18,26). Long-term continuation of maintenance therapy for those in remission can also prevent relapse (18,26).…”
Section: Discussionmentioning
confidence: 90%
“…100 However, while surrogate outcomes have some utility in signaling the presence of inflammatory disease, it has become increasingly less clear the extent to which changing a marker associated with disease alters the course of the disease itself; 'few surrogate markers' have been shown to 'capture the effect of a treatment'. 101 More and more researchers and physicians routinely deprecate evidence devoid of outcomes that matter most to patients and their caregivers (i.e., patient-important outcomes).…”
Section: Surrogate Outcomes For Disease Must Be Carefully Chosenmentioning
confidence: 99%
“…Remission is achievable in around 75-80% of patients after 24 months of treatment (including those with cirrhosis) and associated with around 80% patient survival at 10 years [Montano-Loza et al 2007a;Johnson et al 1995]. Normalization of serum aminotransferase levels within 3 months of starting therapy is highly predictive for sustained biochemical remission at 2 years [Wang et al 2011].…”
Section: Maintaining Remissionmentioning
confidence: 99%